PENGARUH PERSEPSI MAHASISWA TERHADAP KUALITAS PELAYANAN PEGAWAI DIBAGIAN ADMINISTRASI FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING - saputra, trio; utami, bunga chintia; sufi, wasiah (Jurnal Niara, 2018)
The purpose of this study is to determine the effect of student perceptions on the quality of service employees in the administrative department of the administration science universitas lancang kuning. This research is a quantitative research with associative approach. Operational definitions include indicators of student perception variables (X) that accept or absorb, understand or understand and assess or evaluate. Then variable quality of service (Y) that is Tangible, Realiable, Responsiveness, Assurance and Empaty. This study has a population of 90 students in the fourth semester, the sampling technique using randon cluster sampling so the number of samples used in this study is a student IVb semester with the number of 46 people. Data collection techniques used are library research) and field work research. The data gauge used is Likert scale. Data analysis technique used is Simple Linear Regression. The conclusion based on the data analysis and hypothesis testing resulted is the influence of student perceptions on the quality of employee services in the administrative department of the administration science universitas lancang kuning obtained the result of the equation Y = 14.592 + 1.143x and the significance test t of 92%. Then based on the test results of the coefficient of determination of the influence of student perceptions of the quality of service employees in the administrative department of the administration science universitas lancang kuning is 65.8%.